2013
DOI: 10.1002/pbc.24577
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of neoplastic disease in children with isolated pituitary stalk thickening

Abstract: Patients with PST without DI are unlikely to have a neoplastic process. Among patients with DI, APD or progressive stalk increase over time are predictive of neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…In our cohort, the average age of PST patients was 27.6 years and 43.4% of the patients were aged under This result is to some extent in agreement with the evidences shown in a number of previous reports [9][10][11], which stated that patients with PST were mostly between 7 and 13 years old.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our cohort, the average age of PST patients was 27.6 years and 43.4% of the patients were aged under This result is to some extent in agreement with the evidences shown in a number of previous reports [9][10][11], which stated that patients with PST were mostly between 7 and 13 years old.…”
Section: Discussionsupporting
confidence: 93%
“…Since the publication of this report, our decision-making process of treating PST patients was biased in favor of the Hamilton's conclusions. More specifically, we strategically [11]. Our results showed that two-third of polydipsia and polyuria patients were confirmed as diabetes insipidus and about half of the patients were reported to have at least 1 anterior pituitary dysfunction who took the evaluation.…”
Section: Discussionmentioning
confidence: 90%
“…49 In children with isolated DI and a thickened pituitary stalk, the most likely diagnoses are LCH, germ cell tumor, or lymphoma. 50 LCH is frequently a diagnosis of exclusion with normal germ cell markers and normal CSF cytology. Due to risks of pituitary biopsy, in such patients it is reasonable to initiate LCH therapy empirically and monitor for early response by MRI.…”
Section: Brain Mri For Patient With Cns-risk Lesionsmentioning
confidence: 99%
“…Varan et al 19 reported that 69.8% of patients presenting with central DI had the diagnosis of LCH. Infundibular thickening and absence of posterior pituitary intensity were the most common MRI findings 20,21 . We had three patients with DI at the time of diagnosis of MS LCH.…”
Section: Multisystem Lch (Ms-lch) (N:11)mentioning
confidence: 99%